Tingkat Stres Mahasiswa Mengikuti Pembelajaran Daring pada Masa Pandemi Covid-19 - Jannah, Riazul; Santoso, Harri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Nowadays, the Covid-19 pandemic is one of the main health crises for every individual from all nations, all nations, races, and socio-economic groups, the implementation of this lockdown has made very significant changes to the teaching and learning process, one of which is the lecture process as a result of many impacts perceived by the students themselves as less effective. This study aims to describe the problems that occur in students who undergo the learning process bravely during this pandemic. The technique used is a literature review by collecting several existing articles. The results showed that the cause of stress that emerged during the pandemic with a bold learning process was ineffective learning methods, and the conclusions that emerged as a result of the conceptual concept of learning applied in face-to-face learning did not work well.